PRAKTIK CHECK AND BALANCE DALAM KETATANEGARAAN DI INDONESIA ANTARA LEGISLATIF DAN EKSEKUTIF: STUDI KASUS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU- XVIII/2020 - Syamsudin, Syamsudin (LPPM Universitas Bina Bangsa, 2024)
Check and Balance in State Administration is one of the principles in the rule of law that determines and establishes the division of power within a country to prevent the concentration of power in one authority, which can lead to power abuse and corruption. The division of power with limited authority proportionally allows each institution to support and supervise each other, enabling the state's power to be exercised to its maximum potential. In practice, in Indonesia, this can be seen through Constitutional Court Decision Number 91/PUU-XVIII/2020, where there is an imbalance of power within state institutions, even though the balance is appropriately regulated in the constitutional format. This issue is caused by various factors that affect implementation, which is difficult to avoid without firmness from relevant state institutions when carrying out their power obligations. The research method used is normative implementative research, which explains the influence of norms when implemented. Based on Constitutional Court Decision Number 91/PUU-XVIII/2020, it can be concluded that the check and balance system in practice can be influenced by factors that may hinder its effective implementation